2009
DOI: 10.1007/s11307-009-0244-x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Nigrostriatal Pathway in Japanese Encephalitis with Movement Disorders: Evidence from 99mTc-TRODAT-1 and 123I-IBZM SPECT Imagings

Abstract: Data have suggested that presynaptic dopaminergic neurons in JE patients are more susceptible to JE virus than postsynaptic striatal neurons. The degree of movement impairment was more closely correlated to the degree of D2Rs disruption seen in (123)I-IBZM SPECT imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…There are well-documented but rare recent instances in which acute severe encephalitic viral disease was shown to directly cause transient symptomatic PD with evidence of DA neuron–midbrain structural involvement (37) or permanent clinical neurological symptoms, including parkinsonism (3840). However, the central premise of the hypothesis presented here is not that a linear relationship exists between the viral infection, brain inflammation, and an acute manifestation of neurodegenerative disease.…”
Section: Neurons and Glia As Immune Sensorsmentioning
confidence: 99%
“…There are well-documented but rare recent instances in which acute severe encephalitic viral disease was shown to directly cause transient symptomatic PD with evidence of DA neuron–midbrain structural involvement (37) or permanent clinical neurological symptoms, including parkinsonism (3840). However, the central premise of the hypothesis presented here is not that a linear relationship exists between the viral infection, brain inflammation, and an acute manifestation of neurodegenerative disease.…”
Section: Neurons and Glia As Immune Sensorsmentioning
confidence: 99%
“…Liao et al showed the involvement of the nigrostriatal pathway in three JE patients presenting with parkinsonism in Taiwan by single-photon emission tomography (SPECT) using the radiotracer 99m Tc-TRODAT-1 for DAT imaging, and 123 I-iodobenzamide ( 123 I-IBZM) for D2 dopamine receptor imaging (Table 2) (2). All three patients showed bilateral substantia nigra lesions on brain MRI, albeit at different severities, but these did not reflect the corresponding clinical laterality.…”
Section: Discussionmentioning
confidence: 99%
“…Presynaptic striatal dysfunctions recently became detectable by dopamine transporter (DAT) imaging, which is usually applied to neurodegenerative disorders such as Parkinson's disease and progressive supranuclear palsy (PSP). However, there are only limited reports of DAT imaging for JE patients (2,3). In this paper, we report a JE patient that presented with parkinsonism, with decreased DAT imaging using a new radiotracer.…”
Section: Introductionmentioning
confidence: 99%